Geology, geophysics, geochemistry of a hidden Palaeoproterozoic ocean-continent transition in the northern Gawler Craton. Issue 1 (1st December 2018) - Wise, Tom; Pawley, Mark; Thiel, Stephan; Dutch, Rian
Abstract : Craton margins are known to host many major deposit styles across the globe, and constraining the spatial and temporal relation between permissive geometries and thermal drivers for alteration processes are key for identifying prospective terranes. Orthogonal deep crustal reflection seismic profiles provide insight into the three-dimensional crustal architecture of the north-western Gawler Craton, South Australia. Correlating between north-south seismic line 08GA-OM1 and east-west seismic line 13GA-EG1, has enabled the interpretation of a major crustal boundary separating the core of the Gawler Craton from re-worked crustal provinces to the west and north. We use seismic character, potential fields and magnetotellurics to locate and constrain the geometry of this major boundary, and isotopic signatures from sparse drillholes to characterize the crustal age and composition either side of the interpreted boundary. In recent years, isotopic evidence has been used to infer the presence of early Palaeoproterozoic oceanic crust having existed between the Gawler and Yilgarn Cratons. We present a new model for the north-western Gawler Craton, locating a transitional region between a cratonic core and this oceanic crust, and suggest that the craton margin was ~100 km inboard of current interpretations.